Socioeconomic factors associated with divorce rates in Indonesia: Education, Employment, and Poverty - Olivia Nur Fatimah; Soetji Lestari; Nanang Martono (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
Divorce is a social phenomenon that remains one of the most important issues in the world, including in Indonesia. Some residents in Indonesia experience divorce. Data on divorces reported by BPS in 2024 shows that the divorce rate varies in each province. This phenomenon of divorce is caused by several underlying factors. This study aims to analyze the factors that influence divorce, such as average length of schooling, female labour force participation rate, unemployment rate in a region, and percentage of poor people. This study uses quantitative secondary data analysis methods. The data was analysed using product moment correlation calculations. The variables analyzed were the divorce rate; average length of unschooling; female labour force participation rate; unemployment rate; and percentage of poor population. Based on the research results, it shows a positive relationship between average years of schooling and divorce rates; there is a positive relationship between female labor force participation rates and divorce rates; there is a positive relationship between unemployment rates and divorce rates; and there is a positive relationship between the percentage of poor population and divorce rates.